Third way - Thengadi, Dattopant B. (Dattopant Bapurao), 1920-2004.; Shukla, Bhanu Pratap, 1935- (Bangalore : Sahitya Sindhu Prakashana, 1998)
Articles presenting the Hindu approach to economics, technology, environment, and constitutional and legal systems.
Keywords: Social prediction -- India; Economic forecasting -- India; Hinduism; India -- Economic policy -- 1991-; India -- Social policy